Community Reaction towards Social Innovation: A Discussion of Rogers’ Diffusion of Innovations Theory in Consideration of Community Emotional Response - Brian J. Hains; Kristina D. Hains (Journal of International Agricultural and Extension Education, 2020)
While originally utilized within the natural and agricultural sciences, the diffusion of innovation theory has been applied across numerous contexts. As we continue to apply this model within Extension education, international development, and other community education contexts around the world, it not only becomes pertinent to examine how it applies towards social innovations–innovations that improve the social good –but also to understand howcommunities reactwhenadoptingsocial innovations. Within this article, researchers propose an Emotional-Behavioral Influence Modelto deepen theunderstanding as to how communities respond, emotionally and behaviorally, towards social innovationsthroughout the adoption process. They then overlay the model onto twoexamples, one urban and one rural, showcasing its application to communitiesworldwide. Finally, researchers discuss implications for extension professionals as they preflect on implementing social innovations in communities globally
Keywords: Diffusion of Innovationtheory; flow; communities; downshifting; social innovation